PENGARUH PEMBERIAN JERUK NIPIS DAN JAHE MERAH TERHADAP ISPA PADA BALITA DI PMB “R” 2023 - Lisca, Shinta Mona; Handayani, Reni; Hanifah, Fanni (STIKes William Booth Surabaya, 2024)
According to WHO, in 2020 the world's under-five mortality rate will be 10 million people per year. Based on data from the Directorate of Family Health in 2020, ISPA is still the main problem that causes death in children under five. ARI (Acute Respiratory Tract Infection) is an acute infection involving the upper respiratory tract organs and lower respiratory tract organs. ISPA is caused by 55% viruses, 40% bacteria, 5% fungi with symptoms of cough, runny nose and fever. Therapy with lime and red ginger can be an addition to the treatment of ISPA in children under five. Several studies have shown that there is a difference in the length of time it takes to cure ARI in children under five when given lime. Purpose: this research is to determine the effect of giving lime and red ginger on ARI in children under five in PMB R in 2023. Research Method This research uses a qualitative research design with a case study approach Research Results: The conclusion obtained was that giving lime was proven to be effective in curing ISPA in children under five with a difference in recovery time of 3 days faster compared to children under five who were given red ginger. It is hoped that it can provide knowledge, especially for parents, about the effect of giving lime and red ginger on ISPA in children under five. For researchers, it can be an alternative in providing midwifery care in handling ISPA in children under five. Keywords : Toddlers, ISPA, Lime, Red Ginger